Study of the Efficiency of Removal of Lead and Nickel Metals from Effluent Using Two Species of Latifolica and Polygonum Aviculare (Case Study: West Ahwaz Wastewater Treatment Plant) - Mahnaz Moteraghi (Water and Wastewater Consulting Engineers Research Development, 2021)
Due to the water shortage crisis, the reuse of municipal wastewater is essential. Planting plants in the wastewater treatment process is appropriate and can help to reduce and eliminate pollution in urban and rural wastewater. This study aimed to determine the phytoremediation of lead and nickel from Ahwaz wastewater treatment plant. In this study, a completely randomized design with 4 treatments and 3 replications was used, and the laboratory activities were performed in the soil laboratory of Islamic Azad University, Ahvaz Branch. Heavy metals were measured by atomic absorption method and PG Instruments Ltd. The average amount of lead and nickel in the effluent of Ahvaz was 96.35 and 102.57 μg/kg. The amount of lead metal in the studied treatments was 17.85-96.86 ppb, and nickel content was 18.91- 102.87 ppb. In this study, the percentage of the Lewis plant's removal of lead and nickel was 62.66% and 70.18%, respectively. Also, the removal efficiency of the studied parameters by the seven herbaceous plants was 29.26% and 44.22%, respectively. The amount of nickel adsorbed by plants was higher than that of lead metal. The removal efficiency of lead and nickel metals from municipal effluent obtained by Typha Latifolica was higher than Polygonum aviculare. In total, Typha Latifolica and Polygonum aviculare plants had the ability to purify lead and nickel metals from urban effluents so that the amounts of these metals were reduced in the second and fourth treatments within 90 days.